The influence of stereochemically active lone-pair electrons on crystal symmetry and twist angles in lead apatite-2H type structures. (April 2014) - Baikie, T.; Schreyer, M.; Wei, F.; Herrin, J. S.; Ferraris, C.; Brink, F.; Topolska, J.; Piltz, R. O.; Price, J.; White, T. J.
Abstract: Lead-containing (Pb- B-X )-2 H apatites encompass a number of [ A F ]4 [ A T ]6 [( BO 4 )6 ] X 2 compounds used for waste stabilization, environmental catalysis and ion conduction, but the influence of the stereochemically active lone-pair electrons of Pb 2+ on crystal chemistry and functionality is poorly understood. This article presents a compilation of existing structural data for Pb apatites that demonstrate paired electrons of Pb 2+ at both the A F and A T results in substantial adjustments to the Pb F O6 metaprism twist angle, φ. New structure refinements are presented for several natural varieties as a function of temperature by single-crystal X-ray diffraction (XRD) of vanadinite-2 H (ideally Pb10 (VO4 )6 Cl2 ), pyromorphite-2 H (Pb10 (PO4 )6 Cl2 ), mimetite- 2H/M (Pb10 (As 5+ O4 )6 Cl2 ) and finnemanite-2 H (Pb10 (As 3+ O3 )6 Cl2 ). A supercell for mimetite is confirmed using synchrotron single-crystal XRD. It is suggested the superstructure is necessary to accommodate displacement of the stereochemically active 6s 2 lone-pair electrons on the Pb 2+ that occupy a volume similar to an O 2− anion. We propose that depending on the temperature and concentration of minor substitutional ions, the mimetite superstructure is a structural adaptation common to all Pb-containing apatites and by extension apatite electrolytes, where oxide ion interstitials are found at similar positions to the lonepair electrons. It is also shown that plumbous apatite framework flexes substantially through adjustments of the Pb F O6 metaprism twist-angles (φ) as the temperature changes. Finally, crystalchemical [100] zoning observed at submicron scales will probably impact on the treatment of diffraction data and may account for certain inconsistencies in reported structures.